Understanding the structural basis of ALS mutations associated with resistance to sulfonylurea in wheat - Pawan Kumar; Ritika Bishnoi; Pragya Priyadarshini; Parveen Chhuneja; Deepak Singla (Scientific Reports)
Abstract Developing herbicide-tolerant wheat varieties is highly desirable for effective weed management and improved crop yield. The enzyme acetolactate synthase (ALS) is the target enzyme for the sulfonylurea class of herbicides. The structural analysis of mutable sites in ALS is crucial for the generation of herbicide-resistant crops. Previous studies indicated that mutant lines of Triticum aestivum ALS (TaALS) with amino acid substitutions at P174, G631, and G632 residues provided resistance to sulfonylurea herbicide, nicosulfuron. The present study aimed to provide structural insights into mutable residues causing sulfonylurea herbicide resistance to TaALS enzyme through in-silico molecular docking and simulation approaches. The molecular docking analysis suggested a single point mutation at TaALS-P174S, its double mutant conformations (TaALS-G632S/P174S and TaALS-G631D/G632S) and associated triple mutant conformation (TaALS-G631D/G632S/P174S) to have the lowest binding affinity with nicosulfuron than the wild-type conformation of TaALS. Furthermore, the molecular dynamic simulation study confirms the weakest and more stable binding of the triple mutant conformation with nicosulfuron. Our computational study identifies a triple mutant conformation (TaALS-G631D/G632S/P174S) to be more effective in developing sulfonylurea herbicide-resistant wheat crops.